Strategic entrepreneurial ecosystems and business model innovation - Ratten, Vanessa (Emerald Publishing Limited, 2022)
Entrepreneurial ecosystems require business model innovation as part of their evolution. This means when discussing any form of entrepreneurship that involves change, we should consider the role of business models. Strategic Entrepreneurial Ecosystems and Business Model Innovation is the first collection to focus both on entrepreneurial ecosystems and business model innovation, thereby taking a novel and new approach to entrepreneurship and strategic management. Whilst the research on entrepreneurial ecosystems is new the practice has been around for a long time. This means it is important to consider historical developments of entrepreneurial ecosystems with new trends in the form of digitalization. Recognising the need to stress the way business models have altered because of the increase in the knowledge economy, business model innovation is a useful way to consider how entrepreneurial ecosystems develop based on knowledge exchanged in the global business environment. Each chapter of this edited collection focuses on a different area of interest regarding entrepreneurial ecosystems and business model innovation, fusing the literature of both streams of thought in terms of how entrepreneurship evolves based on contextual change.